The upstarts : How Uber, Airbnb, and the killer companies of the new Silicon Valley are changing the world - Stone,Brad (Transworld Publishers, 2017)
The world is changing right before our eyes. Technology has escaped the confines of our computers and mobile devices and has oozed into the real world. We now press a button and summon a cab. We can rent the spare rooms and spare time of others, any time of day. We don't just buy books and movies on-line but groceries, prepared dinners, laundry and babysitting services. This great wave, sparked by the ubiquity of smartphones and high speed internet and cellular networks, has really just started. But the effects and efficiencies of software and the Internet have already upended the industries that once dominated the provision of real-world goods and services. It has minted not just a new set of winners and losers but turned San Francisco into an epicenter of the business world and spawned a new wave of conflict over the inevitable spoils. There is a specific kind of entrepreneurial personality that thrives during unsettled times like this: brash, clever, and almost preternaturally relentless in their focus. They are eternally optimistic about the long-term benefits of technology and yet clinically paranoid about the short-term obstacles and rivals that stand in their way. They break the rules, betray friends, but can be endearingly loyal to the allies who help them achieve their goals. And they are awfully fun to write and read about.